FMR evidence of strong uniaxial anisotropy in La1-xCaxMnO3 - Ramos, C. A. (2012)
We report an electron spin resonance study on La1-xCaxMnO3 ceramic samples with x = 0.33 and 0.5. Below TC the absorption line-shape can be well described as a ferromagnetic resonance with randomly distributed uniaxial anisotropy. In both samples the line-shape is used to fit an average anisotropy value. The anisotropy changes from easy plane for x = 0.33 to easy axis for x = 0.5. The present results for x = 0.5 imply that the uniaxial anisotropy, obtained from the measurements at 100K, is larger than the one expected for shape-only contribution even considering the extreme case of nanowires. The origin and magnitude of this anisotropy are discussed.